A PTEN inhibitor displays preclinical activity against hepatocarcinoma cells. Issue 4 (16th February 2016) - Augello, Giuseppa; Puleio, Roberto; Emma, Maria Rita; Cusimano, Antonella; Loria, Guido R.; McCubrey, James A.; Montalto, Giuseppe; Cervello, Melchiorre
ABSTRACT: Phosphatase and tensin homolog (P TEN ) gene is considered a tumor suppressor gene. However, PTEN mutations rarely occur in hepatocellular carcinoma (HCC), whereas heterozygosity of PTEN, resulting in reduced PTEN expression, has been observed in 32–44% of HCC patients. In the present study, we investigated the effects of the small molecule PTEN inhibitor VO-OHpic in HCC cells. VO-OHpic inhibited cell viability, cell proliferation and colony formation, and induced senescence-associated β-galactosidase activity in Hep3B (low PTEN expression) and to a lesser extent in PLC/PRF/5 (high PTEN expression) cells, but not in PTEN-negative SNU475 cells. VO-OHpic synergistically inhibited cell viability when combined with PI3K/mTOR and RAF/MEK/ERK pathway inhibitors, but only in Hep3B cells, and significantly inhibited tumor growth in nude mice bearing xenografts of Hep3B cells. Therefore, we demonstrated for the first time that VO-OHpic inhibited cell growth and induced senescence in HCC cells with low PTEN expression, and that the combination of VO-OHpic with PI3K/mTOR and RAF/MEK/ERK inhibitors resulted in a more effective tumor cell kill. Our findings, hence, provide proof-of-principle evidence that pharmacological inhibition of PTEN may represent a promising approach for HCC therapy in a subclass of patients with a low PTEN expression.